APPLICATION OF BIRD EGG MORPHOMETRICS IN PHYLOGENY - Mityay, I. S.; Matsyura, A. V.; Jankowski, K. (Acta Biologica Sibirica, 2015)
The aim of this report was to to build phylogenies using bird egg data, because egg data are available for a larger range of species than molecular data, it is cheaper to collect egg data than molecular data, moreover, building trees using egg data provide verification of molecular phylogenies. We used egg morphological data from the collections of zoological museums in Ukraine and Russia. Two models of egg geometry were used: composite ovoid and polynomial. For the first model we used seven indices of description of eggs, including the traditional elongation index as well as six original indices: index of infundibular (blunt) area, index of lateral area, index of local area, index of asymmetry, Equatorial index, and index of complimentary. All the necessary parameters were obtained from the digital pictures of eggs, processed by original computer software in accordance with suggested schemes. Using Falconiformes species as a case study, we found that measures of egg geometry gave important phylogenetic information: egg parameters clearly separated Falconiformes species from Gaviiformes, Pelicanidae, and Podicepediformes. We proposed usage of the morphological parameters of eggs as additional information in bird systematics. Key words: birds, eggs, systematic, geometrical parameters.